Risk factors for serrated polyps of the colorectum - Haque, Tanvir R (Dig Dis Sci, 2014)
Serrated pathway polyps are a relatively new area of interest in the field of colorectal cancer screening and prevention. Akin to conventional adenomas, some serrated polyps (SPs) have the potential to develop into malignant serrated neoplasms, yet little is known regarding risk factors for these lesions. Early epidemiological studies of hyperplastic polyps (HPs) were performed without knowledge of the serrated pathway, and likely included a mixture of SPs. More recently, studies have specifically evaluated premalignant SPs, such as the sessile serrated adenoma (SSA) or surrogates for these polyps such as large or proximally-located SPs. SPs share some risk factors with conventional adenomas, and have been associated with tobacco use, obesity, and age. Nonsteroidal anti-inflammatory drug (NSAID) use, fiber, folic acid, and calcium have been associated with reduced risk of SPs. Studies focused on SSAs specifically have reported associations with age, female sex, smoking, obesity, diabetes, and possibly diets high in fat, carbohydrates, and calories. Higher education has also been associated with risk of SSAs, while an inverse association between NSAID use and SSAs has been reported. Risk factors for traditional serrated adenomas (TSAs) are largely unknown. Studies are largely limited by varying inclusion criteria, as well as differences in pathological classification schemes. Further epidemiological studies of SPs are needed to aid in risk stratification and screening, and etiological research.